A new species of the genus Rhabdophis Fitzinger, 1843 (Squamata: Colubridae) from Guangdong Province, southern China - Zhu, Guang-Xiang; Wang, Ying-Yong; Takeuchi, Hirohiko; Zhao, Er-Mi (Zootaxa, 2014)
A new species, Rhabdophis guangdongensis sp. nov., is described from the Guangdong Province, China. It can be easily distinguished from other known congeners by cyt b and c-mos sequences, and by the following combination of morphological characters: body size small; head distinct from the neck; 20 maxillary teeth, the three most posterior teeth strongly enlarged, and not separated by diastemata from other teeth; six supralabials, the third and fourth touching the eye; seven infralabials, the first four in contact with anterior chin shields; dorsal scales in 15 rows throughout the body, weakly keeled, the outer row smooth; 126 ventrals; 39 paired subcaudals; anal scale divided; 44 pairs of narrow dorsolateral black cross-bars on body and 15 pairs on tail; body and tail with two dorsolateral longitudinal brownish-red lines, respectively with a series of white spots in cross-bars. The description of this new species brings the total number of described species of this genus to 21 and represents the tenth known Rhabdophis species in China.